Association between exercise capacity and health markers in adolescents - Mani, Chandra; Ghildiyal, Archna; Singh, Shraddha; Mittal, Anupam; Ansari, Aaqib Husain (International Journal of Research in Medical Sciences, 2024)
Background: Adolescent physical fitness is a crucial determinant of current and future health, influencing susceptibility to chronic diseases such as cardiovascular conditions and diabetes. The American Heart Association highlights cardiorespiratory endurance as a vital health metric, emphasizing the need for regular physical activity to mitigate long-term health risks. Methods: A cross-sectional observational study was conducted from 24 March 2023 to 20 March 2024 in the Lucknow city, India. Total 411 adolescents recruited from local school camps and adolescent clinics. Participants underwent a series of assessments, including the 6-minute walk test (6-MWT) to evaluate functional capacity and endurance, body fat analysis using the body stat 1500 MDD machine, and anthropometric measurements. Tabulated data were statistically analysed to find any relationships between BMI, body fat composition, and physical performance. Results: The study revealed significant correlations between BMI and body fat percentage (p<0.0001) and between BMI and body fat in kilograms (p<0.0001). Increased body fat percentage and fat mass was associated with higher BMI. The mean distance covered in the 6-MWT was 918.85 meters, with significant variability across gender. Body composition metrics indicated that higher BMI categories were associated with increased fat-free mass (p<0.0001). Conclusions: This study underscores the critical need for targeted interventions to address physical inactivity and obesity in adolescents. By improving physical fitness and body composition, it is possible to mitigate health risks and promote better long-term health outcomes.